Short Course Radiotherapy Concomitant with Temozolomide in GBM Patients: A Phase II Study. Issue 5 (September 2017) - Fariselli, Laura; Cuppini, Lucia; Gaviani, Paola; Marchetti, Marcello; Pinzi, Valentina; Milanesi, Ida; Simonetti, Giorgia; Tramacere, Irene; DiMeco, Francesco; Salmaggi, Andrea; Silvani, Antonio
Purpose: Despite recent advances, the prognosis of glioblastoma (GBM) remains poor. The aim of this study was to assess the efficacy and tolerability of multiple daily fraction radiotherapy performed with multiple temozolomide (TMZ) administrations in newly diagnosed patients with GBM. Methods: This trial was a prospective, open-label, monocentric, nonrandomized, single arm, phase II study. The primary endpoint was the proportion of progression-free patients at 12 months, and the secondary endpoints were overall survival (OS) and toxicity. Thirty-five patients underwent two radiotherapy courses concomitant with TMZ after surgery. At each course, radiation was delivered 3 times daily, 2 Gy/fraction, for 5 consecutive days, and the total dose was 60 Gy; concurrent TMZ was administered in a total dose of 150-200 mg/m 2 /day. Results: The primary endpoint failed to be applied; Macdonald criteria could be used in 16 (46%) patients with local or intracerebral recurrence (group A). In 12 patients, due to suspicion of radiation necrosis vs recurrence, Macdonald criteria were not applied (group B). The OS was 22 months, and OS probabilities at 12, 18, and 24 months were 82%, 59%, and 44%, respectively. Hematologic toxicities generally did not exceed grade 2. The quality of life and cognitive functioning did not significantly change between baseline and the first follow-up. In the multivariate analysis, necrosis and pseudoprogression were significant prognostic factors of OS. Conclusions: To improve local control and OS, a more aggressive treatment schedule should be explored. The related higher necrosis risk and its implications regarding local control deserve further investigation.